Flash sale: How young people practice dromology in digital consumption - Rahmah, Hilda; Julianto, Edi Nurwahyu; Suhariyanto, Suhariyanto (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
This study analyzes chronological practices in flash sale activities by digital natives in the Shopee Market Place. Flash Sale is a program that offers price promotions with limited stock and time. Flash sale activities provide a lot of ease of access, especially among young people to meet their needs, but this also has the consequence of media dependence, even to the point where consumers are trapped in simulacra that makes them lose their ability to distinguish between wants and needs. This study uses the nethnography method to collect data related to 3:3 and 4:4 flash sale activities on Shopee in March and April 2024, where the subjects in this study were active Shopee users aged 19-26 years who were involved in the 3:3 and 4:4 flash sale program transactions. The results of the study show that chronological practices carried out by young people in flash sale activities include physical boundaries, mediated reality, totally involuntary war, and end colonization. Research data analysis shows that young people in flash sale activities are in the digital youth category, with dystopian, futurist, and techno-realist types. Flash sale is a dromology or acceleration phenomenon that can control consumer anxiety and give rise to a desire to compete. This group is very vulnerable to being targeted by digital capitalists in creating a space of enjoyment, which is unknowingly fake.